Immunoglobulin G4-related pleuritis – A case report - Gajewska, Marta E. (Respir Med Case Rep, 2016)
Immunoglobulin G4-related disease (IgG4-RD) is a chronic disease that presents with inflammation and fibrosis of involved tissue. It encompasses several disorders previously described using different terms, but all disorders are characterised by IgG4-positive plasma cells and lymphocytes infiltration of tissues. We report a rare case of a 58-year-old man with IgG4-related pleural disease without other systemic manifestations. The diagnosis was based on characteristic changes on PET-CT and typical histopathology in a pleural specimen. The patient’s condition improved following immunosuppressive therapy.